Pemberdayaan Guru Madrasah Ibtidaiyah melalui Transformasi Manajemen Mutu Sumber Daya Manusia Guna Meningkatkan Mutu Madrasah Se-Kecamatan Diwek Kabupaten Jombang - Mardiyah; Lailatul Qamariyah; Abdullah Aminuddin Aziz (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2016)
The success of education at the school is largely determined by success in managing the head of the educational staff in schools/madrasah. Principals have responsibility for improving the quality of teachers in achieving its objectives in addition to the government's obligations. Implementation of management education personnel (teachers and staff) in Indonesia according Mulyasa, at least include; workforce planning, procurement personnel, dismissal of personnel, coaching and development, promotion and assessment. Activities meant to show that the provision of teachers as educators very great concern in efforts to achieve the quality of the success of learners. Quality Management aims to develop human resources empowerment of teachers who are expected to engage actively pushing to improve the quality of schools/madrasah. This devotion performed on MI Urwatul Wusqo PP. Al-Urwatul Wutsqo Bulurejo, MI Perguruan Muallimat in PP Walisongo Cukir, MI Tarbiyatul Aulad Bandung in Gebang Malang Bandung and MI Ar-Rohman Nglaban Bendet. Relative activity of teacher empowerment through developing quality human resources management model in order to improve the quality of madrasah in Sub district Diwek Jombang, can be summarized as follows: 1. In the beginning, the madrasah four management models are clerical, after empowering the community service program, the fourth madrasah management models to increase to managerial model. 2. Subject devotion capable of implementing the quality management model of human resources fitted to the characteristics of each institution. 3. The quality of human resources management model developed by Principals effective enough to increase the empowerment of teachers in the fourth MI. 4. The research subjects were able to understand the quality of human resources management capabilities and strength of institutions in improving teacher quality through the transformation of the quality management of human resources. 5. The research subjects understand their duties and functions as teachers (institution Asset, facilitator, motivator, mediator, and creator) in the teaching and learning process